Role of a Genetic Polymorphism in the Corticotropin-Releasing Factor Receptor 1 Gene in Alcohol Drinking and Seeking Behaviors of Marchigian Sardinian Alcohol-Preferring Rats - Ayanwuyi, Lydia O.; Carvajal, Francisca; Lerma-Cabrera, Jose; Domi, Esi; Bjork, Karl; Ubaldi, Massimo; Heilig, Markus; Roberto, Marisa; Ciccocioppo, Roberto; Cippitelli, Andrea (Frontiers in Psychiatry, 2013)
Marchigian Sardinian alcohol-preferring (msP) rats exhibit innate preference for alcohol, are highly sensitive to stress and stress-induced alcohol seeking. Genetic analysis showed that over-expression of the corticotropin-releasing factor (CRF) system of msP rats is correlated with the presence of two single nucleotide polymorphisms (SNPs) occurring in the promoter region (position -1836 and -2097) of the CRF1 receptor (CRF1-R) gene. Here we examined whether these point mutations were associated to the innate alcohol preference, stress-induced drinking and seeking. We have recently re-derived the msP rats to obtain two distinct lines carrying the wild type (GG) and the point mutations (AA), respectively. The phenotypic characteristics of these two lines were compared with those of unselected Wistar rats. Both AA and GG rats showed similar patterns of voluntary alcohol intake and preference. Similarly, the pharmacological stressor yohimbine (0.0, 0.625, 1.25 and 2.5 mg/kg) elicited increased operant alcohol self-administration under fixed and progressive ratio reinforcement schedules in all three lines. Following extinction, yohimbine (0.0, 0.625, 1.25 and 2.5 mg/kg) significantly reinstated alcohol seeking in the three groups. However, at the highest dose this effect was no longer evident in AA rats. Treatment with the CRF1-R antagonist antalarmin (0, 5, 10 and 20 mg/kg) significantly reduced alcohol-reinforced lever pressing in the AA line (10 and 20 mg/kg) while a weaker or no effect was observed in the Wistar and the GG group, respectively. Finally, antalarmin significantly reduced yohimbine-induced increase in alcohol drinking in all three groups. In conclusion, these specific SNPs in the CRF1-R gene do not seem to play a primary role in the expression of the msP excessive-drinking phenotype or stress-induced drinking but may be associated with a decreased threshold for stress-induced alcohol seeking and an increased sensitivity to the effects of pharmacolo